Exploring Sistem Informasi Akuntansi Aplikasi GoCar Di Palembang - Lesi Hertati; Iriyadi Iriyadi (Jurnal Ilmiah Akuntansi Kesatuan, 2023)
The purpose of this study is to determine the effect of business ethics; business process; technology to information; accounting information system. The background of this research is the importance of appropriate information technology as an important factor in improving the quality of accounting information systems. The population of this study are users of the Gocar application, namely online drivers to provide convenience to Gocar service users with advances in information technology enabling users to adopt more sophisticated and integrated information systems. Using the right technology, such as the latest accounting software or a secure database system and reliable accounting information systems will provide long-term benefits. This descriptive analysis examines the effect of constructs such as better decision making. In a business world that depends on technology, it is important for organizations to apply good business ethics, improve PR efficiency which is very important for business processes, and make optimal use of information technology to optimize the accounting information system in the GoCar application. Keywords: Business Ethics; Business process; Information Technology; Accounting information system; Technology Applications.